2006
DOI: 10.1002/ps.1152
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity against Panonychus citri of a ginkgolic acid from the external seed coat of Ginkgo biloba

Abstract: An acaricidal substance extracted from the external seed coat of Ginkgo biloba L. was identified by UV (ultraviolet), IR (infrared), EI-MS (electron impact ion source mass spectrometry), (1)H NMR (nuclear magnetic resonance) and (13)C NMR as 6-[(Z)-10-heptadecenyl]-2-hydroxybenzoic acid (compound 1). Laboratory bioassay on citrus red mite, Panonychus citri (Mcg), showed that compound 1 possessed the following properties. (i) Powerful contact toxicity with an LC(50) of 5.2 mg litre(-1) after 24 h that was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…It was also shown that 6-[(Z)-10-heptadecenyl]-2-hydroxybenzoic acid from the external seed coat of G. biloba has an acaricidal activity against Panonychus citri. The contact toxicity of this compound was similar or significantly superior to those of pyridaben and omethoate, systemic insecticidal and acaricidal compounds [168]. Phenolic lipids also exhibit larvicidal activity.…”
Section: Phenolic Lipids Inhibit Bacterial Fungal Protozoan and Pamentioning
confidence: 77%
“…It was also shown that 6-[(Z)-10-heptadecenyl]-2-hydroxybenzoic acid from the external seed coat of G. biloba has an acaricidal activity against Panonychus citri. The contact toxicity of this compound was similar or significantly superior to those of pyridaben and omethoate, systemic insecticidal and acaricidal compounds [168]. Phenolic lipids also exhibit larvicidal activity.…”
Section: Phenolic Lipids Inhibit Bacterial Fungal Protozoan and Pamentioning
confidence: 77%
“…In Xingasn (Guangxi Province, PR China), fruit juice produced during the peeling process was diluted with water and used as an insecticide by local peasants. Satisfactory results were achieved in the control of many kinds of insects [3,5,6] .…”
Section: Introductionmentioning
confidence: 92%
“…As a result of this disposal, the soil and water became polluted, poisoning the organisms living within. However, the seed coat also contains many useful constituents [3,4] . In Xingasn (Guangxi Province, PR China), fruit juice produced during the peeling process was diluted with water and used as an insecticide by local peasants.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated the acaricidal activity against this mite of a ginkgolic acid, 6-[(Z)-10heptadecenyl]-2-hydroxybenzoic acid, isolated from the external seed coat of Ginkgo biloba [54]. Laboratory bioassays showed that this compound possessed powerful contact toxicity, similar to that of pyridaben and significantly superior to that of omethoate.…”
Section: Agriculturementioning
confidence: 99%